A New Proposal for Consumer Price Index (CPI) Calculation and Income Distribution Measurement by Income Groups - Esat Daşdemir (Journal of Economy Culture and Society)
This study examines the calculation of consumer price index (CPI) according to income groups. One of the principal determinants of consumption habits is income level; therefore, individuals’ consumer goods baskets change according to income level. In this context,the inflation rates faced differ according to income levels. Using Turkish Statistical Institute data, this study demonstrates that individuals with low-income levels faced higher inflation rates between the years 2006– 2021 in the Republic of Turkey than those in the high-income group; therefore, even if income level remains constant, the difference in living standards between low- and high-income groups has widened due to this inflation difference. Accurate determination of income distribution and income inequality is essential for social policy planning. Consequently, including changes in purchasing power is recommended in income distribution analysis. This study proposes an alternative method for the calculation of income distribution using the Gini coefficient. For the utilization of this method, separate CPI calculations are conducted for each income group using consumer goods baskets representing various income groups. The study contributes to the literature with a novel critique of current methods of CPI and income distribution, proposing an approach to address this criticism. In this respect, the findings and proposed approach could serve as a reference for policymakers’ development and implementation of social policies.